2017
DOI: 10.1016/j.wasman.2017.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical pretreatment of waste paper for biogas production

Abstract: In the anaerobic digestion of lignocellulosic materials such as waste paper, the accessibility of microorganisms to the fermentable sugars is restricted by their complex structure. A mechanical pretreatment with a Hollander beater was assessed in order to reduce the biomass particle size and to increase the feedstock' specific surface area available to the microorganisms, and therefore improve the biogas yield. Pretreatment of paper waste for 60min improves the methane yield by 21%, from a value of 210ml/gVS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 42 publications
(39 reference statements)
4
37
0
Order By: Relevance
“…Mechanical pretreatment is well-known method to improve biogas production, however it is yet considered to be an expensive method, due its high energy requirements [62]. The size reduction of lignocellulosic biomass is an essential step to increase the accessible surface area and the porosity of the particles, besides reducing the crystallinity of the cellulose and improves the efficiency of the next processing step and global production chain [63]. One advantage of mechanical pretreatment is that it does not produce any secondary inhibitory substances, which suggest that could be suitable for methane production or any other bioprocess [64].…”
Section: Mechanicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical pretreatment is well-known method to improve biogas production, however it is yet considered to be an expensive method, due its high energy requirements [62]. The size reduction of lignocellulosic biomass is an essential step to increase the accessible surface area and the porosity of the particles, besides reducing the crystallinity of the cellulose and improves the efficiency of the next processing step and global production chain [63]. One advantage of mechanical pretreatment is that it does not produce any secondary inhibitory substances, which suggest that could be suitable for methane production or any other bioprocess [64].…”
Section: Mechanicalmentioning
confidence: 99%
“…On the other side, the processing time on particle reduction is not only important in energy terms, but also influence the efficiency of the bioconversion of lignocellulosic biomass [59]. Rodríguez et al [63] compared 30 and 60 min of mechanical pretreatment, and reported a 21% increase in methane yield for 60 min and that 30 min pretreatment did not improve the methane yield. For the cost reduction of the energy involved in mechanical pretreatments, the speed of the milling equipment must be considered [72].…”
Section: Mechanicalmentioning
confidence: 99%
“…Landfilling of these wastes is still the most common practice in the world [2], resulting in pollution of water and soil with leachate, and air with emission of methane and other greenhouse gases [3,4]. Anaerobic digestion to produce biomethane has been a successful treatment option for these wastes; it is effective in solving environmental, health and energy challenges [3][4][5]. Additionally, the digestate residues from biogas plants are rich in macro-and micronutrients and also contain phosphorus and ammonium nitrogen [6], which make them suitable as biofertilizers [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the recalcitrant structure of PW makes it difficult for the microorganisms to breakdown this substrate and produce biomethane. Consequently the hydrolysis step is the rate-limiting step in the AD process when treating these lignocellulose-rich wastes [5]. In view of this point, there is a need to determine suitable dry AD process conditions for effective biogas production from PW.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the adequate precession ratio in the ANOVA response surface linear model is above 4, which specifies that the entire model is very adequate and as a sign good model discrimination. However, for a model to be adequate, the model reduction will certifies and significantly accept the essential statistical analysis to carry out an optimization process [49]. The final equation for the experimental parameters and actual factors, as determined by the software is shown in Equation 1 1where: P is the pressure N is the number of passes R is the reaction time As shown in Table 3, there are three interaction terms that have a significant effect on the amount of lipid produced, which are: pressure, number of passes and reaction time.…”
Section: Introductionmentioning
confidence: 99%